"ROOTS OF RHYTHM: MUSICAL INSTRUMENTS OF EAST AFRICA", video with booklet, Jacaranda Designs Ltd, Nairobi, 1995. - Tracey, Andrew (International Library of African Music, 1996)
pages: 148
Keywords: African Music